(untitled) (Latakia University Journal -Biological Sciences Series, 2025)
This study examined the abundance of a group of marine protozoa, namely ciliates, and specifically the Tintinnids group, in the southern coastal area of ​​the Lattakia city between the Al-Kabir Al-Shamali River estuary and the fishing port on the southern beach. Four different stations were selected in terms of the chemical characteristics of the studied water from sewage contamination, fishing vessel tailings or proximity to the estuary, as well as a station somewhat distant from the sources of pollution. Six cruses were conducted between February and October of 2017. Ciliates were sampled from the surface seawater by horizontal hauls using a WP2 plankton net with 50 microns holes diameter. The results showed that the abundance of ciliates from the Tintinnids group had clear differences throughout the year, and its value ranged between (4-154) individuals/m3, and was characterized by the presence of two peaks, one in the spring and the other in the fall. The results also showed an increase in the abundance value in April 2017 at the station (ST4) near the river estuary compared to the rest of the stations. This is due to the dominance of two species of these studied organisms, as well as to their exposure to more nutrients coming from the river estuary. The variable effect of pollutants and nutrients at some stations has affected the abundance of these organisms compared to their abundance in non-contaminated areas. The nature of these studied organisms is characterized by their high sensitivity to environmental variables and the chemical characteristics of the water layer, as well as the difference between species in the face of these variables, and this is clearly evident among the stations affected by the pollution sources.